Preparation method of modified PTFE fluorine film material, fluorine film material and wind power blade

Through the preparation of modified PTFE fluorine film materials, the non-stickness and creeping problems of fluorine film materials on wind power blades are solved, and the viscosity and tensile strength of the material are improved, meeting the technical requirements and weight reduction of wind power blades are achieved. This requirement.

CN119192645APending Publication Date: 2024-12-27CHINA MING YANG WIND POWER GRP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411297256.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing fluorine film materials have non-stickness and creep problems on wind power blades, which cannot achieve effective bonding process operations, and lead to relaxation of the film surface during long-term use, affecting the aerodynamic shape of the blades.

Method used

By preparing a modified PTFE fluorine film material, polymerization reaction is carried out using TFE monomer, deionized water, dispersant, stabilizer and initiator, and a low viscosity PTFE emulsion is added to prepare, and the modified agent is added, and the PTFE emulsion is prepared by drying, baking and sintering. Treatment, combined with the film surface treatment agent, improves the adhesion and tensile strength of the material, and reduces the creep elongation.

Benefits of technology

The adhesive properties of the material are realized, the interface bonding ability between the film material and epoxy adhesive is improved, the creep elongation is reduced, the long-term application needs of wind power blades are met, and the blade weight and cost are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192645A_ABST
    Figure CN119192645A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a modified PTFE (polytetrafluoroethylene) fluorine film material, the fluorine film material and a wind power blade. The preparation method comprises the following steps: preparing PTFE emulsion; drying, baking and sintering the PTFE emulsion to obtain a PTFE membrane material; preparing a membrane material surface treating agent; and coating the PTFE membrane material with the membrane material surface treating agent, and drying, baking and sintering the PTFE membrane material to obtain the modified PTFE fluorine membrane material. Through the development and design of the formula of the fluorine film material and the surface treatment process, the limitation of the fluorine film material applied to the blade is solved, the original non-sticky property of the material is adjusted to be sticky, meanwhile, the creep property of the material is greatly reduced, the tensile strength of the material is improved, innovative application to the blade is achieved, and the service life of the blade is prolonged. And finally, the technical requirements of application to the blade and the requirements of weight reduction and cost reduction are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fluorine membrane material modification and innovative application, and in particular to a preparation method of a modified PTFE fluorine membrane material, a fluorine membrane material and a wind turbine blade. Background Art

[0002] As wind turbine blades become larger, their weight increases, and the corresponding manufacturing cost increases. Traditional structural design optimization and material usage optimization and adjustment methods are getting closer and closer to the limit of blade weight reduction and cost reduction. Therefore, it is necessary to introduce lighter and less-used materials as blade structural materials to replace the existing blade main structural materials, so as to fundamentally achieve blade structural innovation and weight reduction and cost reduction.

[0003] The main component of the fluorine membrane material is PTFE (polytetrafluoroethylene), which has the advantages of low surface density (about 500-1000 g / m2), thin thickness (about 0.5-1.0 mm), high strength (breaking tensile strength 4000-8000 N / 5 cm), high modulus (tensile modulus 3-5 GPa), etc. It meets the performance requirements of blade structure design, can realize lightweight design of blades, and meet the durability requirements of long-term application on blades.

[0004] However, due to the material properties, the current fluorine membrane materials have the following two performance deficiencies:

[0005] 1. The surface is non-sticky and has the lowest surface tension among solid materials. It does not adhere to any substance, so it is impossible to implement the bonding process on the blade;

[0006] 2. The material has creep properties. Under long-term tensile conditions, the membrane material exhibits nonlinear characteristics, and the woven structure determines that the material has creep properties. It will tend to slowly stretch over time and produce irreversible permanent deformation. When the membrane material applies a preload on the blade, the negative effect of stress relaxation on the membrane surface will occur, affecting the aerodynamic shape of the blade. Summary of the invention

[0007] The first purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a modified PTFE fluoromembrane material. By developing and designing the formula of the fluoromembrane material and the surface treatment process, the limitations of the application of the fluoromembrane material on blades are solved, and the material is adjusted from the original non-stickiness to a sticky property. At the same time, the creep characteristics of the material are greatly reduced, the tensile strength of the material is improved, and innovative applications on blades are realized, ultimately meeting the technical requirements for application on blades and the needs of weight reduction and cost reduction.

[0008] The second object of the present invention is to provide a modified PTFE fluorine membrane material.

[0009] A third object of the present invention is to provide a wind turbine blade.

[0010] The first object of the present invention is achieved by the following technical solutions:

[0011] A method for preparing a modified PTFE fluorine membrane material comprises the steps of:

[0012] Putting TFE monomer, deionized water, a first dispersant, a stabilizer and an initiator into a reactor according to a preset ratio to carry out a polymerization reaction, and adding a modifier into the reactor when the polymerization reaction reaches a preset time to prepare a PTFE emulsion with low viscosity;

[0013] Drying, baking and sintering the PTFE emulsion to obtain a PTFE membrane material;

[0014] The second dispersant and deionized water are mixed and stirred at a preset temperature according to a preset ratio, and then cooled to room temperature to prepare a mixed liquid, and a softener, a perfluoro copolymer resin dispersion and a defoamer in a preset ratio are sequentially added to the mixed liquid and stirred evenly to obtain a membrane surface treatment agent;

[0015] The membrane surface treatment agent is coated on the PTFE membrane material, and the PTFE membrane material is dried, baked and sintered to obtain a modified PTFE fluorine membrane material.

[0016] Furthermore, the specific steps of adding TFE monomer, deionized water, the first dispersant, the stabilizer and the initiator into a reactor according to a preset ratio for polymerization reaction, and adding a modifier into the reactor when the polymerization reaction reaches a preset time to prepare a PTFE emulsion with low viscosity are as follows:

[0017] Put TFE monomer, deionized water, a first dispersant, a stabilizer and an initiator into a reaction kettle according to the ratio of 10,000 parts of TFE monomer, 5,000 to 20,000 parts of deionized water, 2 to 20 parts of the first dispersant, 100 to 1,000 parts of the stabilizer and 0.1 to 1 part of the initiator to carry out a polymerization reaction;

[0018] Control the reaction temperature in the reactor to be 40°C to 90°C, the pressure to be 2 to 5MPa, the stirring speed to be 50 to 200r / min, and the reaction time to be 6 to 24h;

[0019] When the polymerization reaction time reaches 50% to 80%, 1 to 10 parts of a modifier are added into the reactor to prepare a PTFE emulsion with low viscosity.

[0020] Furthermore, the first dispersant is one of peralkyl carboxylates, fluoroalkyl carboxylates, and perfluorooctane sulfonates; the stabilizer is a water-insoluble saturated hydrocarbon with more than 12 carbon atoms; the initiator is an ionic inorganic initiator; and the modifier is perfluoromethyl vinyl ether, perfluoroethyl vinyl ether, perfluoropropyl vinyl ether, or perfluorobutyl vinyl ether.

[0021] Furthermore, the specific steps of drying, baking and sintering the PTFE emulsion to obtain the PTFE membrane material are as follows:

[0022] S201, filling PTFE emulsion into each dipping tank of the first coating equipment, allowing the plain glass fiber cloth to flow from the initial position through each dipping tank through the winding and rolling action of the roller of the first coating equipment, so that the surface of the plain glass fiber cloth is coated with PTFE emulsion due to dipping, and then sintering the PTFE emulsion on the surface of the plain glass fiber cloth through the treatment of the drying area, baking area, and sintering area of ​​the first coating equipment;

[0023] S202, repeating step S201 for a preset number of times according to the thickness requirement of the PTFE membrane material to obtain the PTFE membrane material.

[0024] Furthermore, the temperature of the drying zone is 80°C to 95°C, the temperature of the baking zone is 250°C to 315°C, and the temperature of the sintering zone is 360°C to 400°C.

[0025] Furthermore, the second dispersant and deionized water are mixed and stirred at a preset temperature according to a preset ratio, and then cooled to room temperature to prepare a mixed liquid, and a softener, a perfluoro copolymer resin dispersion and a defoaming agent in a preset ratio are sequentially added to the mixed liquid and stirred evenly to obtain a membrane surface treatment agent. The specific steps are as follows:

[0026] The second dispersant and deionized water are mixed and stirred at 50°C to 80°C according to a preset ratio until the second dispersant is evenly dissolved, and the mixture is cooled to room temperature to form a mixed liquid, and then a softener, a perfluoro copolymer resin dispersion and a defoamer are sequentially added to the mixed liquid according to a preset ratio, stirred evenly, and filtered using a mesh screen to obtain a membrane surface treatment agent;

[0027] The preset ratio is: 100 parts of perfluoro copolymer resin dispersion, 1 to 5 parts of second dispersant, 0.1 to 1 part of defoaming agent, 0.1 to 2 parts of softener, and 10 to 100 parts of deionized water.

[0028] Furthermore, the perfluoro copolymer resin dispersion is one or two of a fluorinated ethylene propylene copolymer and a tetrafluoroethylene-perfluoro copolymer with a mass content between 40% and 60%; the second dispersant is a nonionic surfactant; the defoamer is a modified polysiloxane defoamer; and the softener is a silicone resin with a methanol functional group.

[0029] Furthermore, the specific steps of coating the membrane surface treatment agent onto the PTFE membrane material, and drying, baking and sintering the PTFE membrane material to obtain the modified PTFE fluorine membrane material are as follows:

[0030] The membrane surface treatment agent is filled into each dipping tank of the second coating equipment, and the PTFE membrane is passed through each dipping tank from the initial position through the winding and rolling action of the roller of the second coating equipment, so that the surface of the PTFE membrane is coated with the membrane surface treatment agent due to dipping, and then the surface of the PTFE membrane is sintered into a surface treatment layer of a preset thickness after being treated in the drying area, baking area and sintering area of ​​the second coating equipment, thereby finally obtaining a modified PTFE fluoromembrane material.

[0031] The second object of the present invention is achieved by the following technical solutions:

[0032] A modified PTFE fluorine membrane material is prepared by the method described above.

[0033] The third object of the present invention is achieved by the following technical solutions:

[0034] A wind turbine blade comprises the modified PTFE fluoromembrane material, wherein the modified PTFE fluoromembrane material is arranged in the trailing edge shell area of ​​the wind turbine blade by bonding, and is located between the main beam and the trailing edge beam of the wind turbine blade. The middle area of ​​the modified PTFE fluoromembrane material is supported by transverse ribs in the axial direction of the wind turbine blade.

[0035] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0036] 1. The modified PTFE fluoromembrane material proposed in the present invention can adjust the material surface from non-sticky to sticky, greatly improving the interface bonding ability between the membrane material and the epoxy adhesive, and meeting the bonding process and performance requirements on wind turbine blades.

[0037] 2. The modified PTFE fluoromembrane material proposed in the present invention can greatly reduce the creep elongation of the material to below 0.1%, meeting the creep performance requirements of the material when used on blades for more than 20 years, and minimizing the impact of the stress relaxation of the membrane material on the aerodynamic performance of the blade.

[0038] 3. The modified PTFE fluoromembrane material proposed in the present invention is applied to blades to replace the fiberglass skin material in the trailing edge area, which can reduce the weight of the blades by about 10-20% and the material cost by about 5-10%. The reduction in the load of the blades on the whole machine will further achieve the economic benefits of reducing the weight and cost of the whole machine, and ultimately reduce the electricity cost of the wind turbine operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of the structure of modified PTFE fluoromembrane material replacing the fiberglass in the trailing edge area of ​​a wind turbine blade.

[0040] Figure 2 This is a schematic cross-sectional view of the trailing edge area of ​​a wind turbine blade after coating with modified PTFE fluoromembrane material.

[0041] Figure 3 It is the internal structure of the bonding area at the trailing edge of the wind turbine blade.

[0042] Figure 4 Schematic diagram of the processing process of modified PTFE fluoromembrane material. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0044] Embodiment 1:

[0045] This embodiment provides a method for preparing a modified PTFE fluorine membrane material, comprising the steps of:

[0046] S1-1, 10,000 parts of TFE monomer, 10,000 parts of deionized water, 5 parts of a first dispersant (ammonium perfluorooctanoate), 500 parts of a stabilizer (paraffin), and 0.5 parts of an initiator (ammonium persulfate) are put into a reactor to carry out a polymerization reaction;

[0047] The reaction temperature in the reactor was controlled to be 60°C, the pressure to be 3.5MPa, the stirring speed to be 100r / min, and the reaction time to be 10h;

[0048] When the polymerization reaction time reached 70%, 5 parts of a modifier (PMVE) were added into the reactor to prepare a PTFE emulsion with low viscosity.

[0049] S1-2, drying, baking and sintering the PTFE emulsion to obtain a PTFE membrane material; the specific steps are as follows:

[0050] S1-201, fill the PTFE emulsion into each dipping tank of the first coating device 5, such as Figure 4As shown, the plain glass fiber cloth is wound and rolled by the roller of the first coating device 5 from the initial position through each dipping tank, so that the surface of the plain glass fiber cloth is coated with PTFE emulsion due to dipping, and then the PTFE emulsion is sintered and formed on the surface of the plain glass fiber cloth through the drying area, baking area, and sintering area of ​​the first coating device. After each emulsion dipping and high-temperature treatment, the PTFE coating can achieve a certain thickness increase.

[0051] S1-202, repeat the above steps for a preset number of times according to the thickness requirement of the PTFE membrane material to obtain the PTFE membrane material.

[0052] The temperature of the drying zone is 80°C, which is used to remove moisture from the emulsion coating; the temperature of the baking zone is 280°C, which is used to remove the coating surfactant; and the temperature of the sintering zone is 380°C, which is used for sintering and molding the PTFE coating. At the same time, the coating processing flow rate is set to 0.5 m / min. Too slow a speed will lead to a decrease in production efficiency and economic benefits, while too fast a speed may also cause the presence of coating blisters due to insufficient removal of moisture in the drying zone or insufficient removal of surfactants in the baking zone, which may increase the risk of fire in the sintering zone, as well as the risk of insufficient sintering and affecting product performance.

[0053] S1-3, 3 parts of the second dispersant (Triton X-100) and 50 parts of deionized water were mixed and stirred at 70°C until the second dispersant was evenly dissolved and cooled to room temperature to form a mixed solution, and then 1 part of a softener (organic silicone resin containing alcohol hydroxyl functional groups (CH2)3OH-(CH3)2SiO 0.5 ), 100 parts of a perfluoro copolymer resin dispersion (FEP emulsion) with a mass content of 48% and 0.3 parts of a defoaming agent (BYK-024), stir evenly, and filter using a 200-mesh sieve to obtain a membrane surface treatment agent.

[0054] S1-4. Fill the membrane surface treatment agent into each dipping tank of the second coating equipment, and let the PTFE membrane flow from the initial position through each dipping tank through the winding and rolling action of the roller of the second coating equipment, so that the surface of the PTFE membrane is coated with the membrane surface treatment agent due to dipping, and then use a scraper to remove excess treatment agent. Then, after passing through the drying area, baking area, and sintering area of ​​the second coating equipment, the surface of the PTFE membrane is sintered into a thin surface treatment layer. The thickness of the surface treatment layer is 30um, thereby finally obtaining a modified PTFE fluoromembrane material with good mechanical strength, creep performance and adhesion performance.

[0055] In the actual preparation process, the first dispersant can be selected from one of peralkyl carboxylates, fluoroalkyl carboxylates, and perfluorooctane sulfonates, such as ammonium perfluorooctanoate and ammonium perfluorononanoate. The first dispersant can make the polymerization monomers evenly distributed, and the amount added should be sufficient to ensure that no agglomeration occurs during the polymerization process, but not too much to avoid causing the primary particles to be too small, affecting the molecular weight of the final product.

[0056] The stabilizer is also called an anti-agglomeration agent and is a water-insoluble saturated hydrocarbon having a carbon number of 12 or more. For example, paraffin is used in this embodiment, which is liquid at the polymerization temperature.

[0057] The initiator is used to initiate the polymerization reaction, and an ionic inorganic initiator such as ammonium persulfate or alkali metal persulfate such as potassium persulfate, lithium persulfate, etc. is used, which is suitable for a temperature range of 40 to 90°C. The amount of the initiator should not be too high or too low, otherwise it will significantly reduce the molecular weight of the product if it is too high, and it will significantly increase the molecular weight of the product if it is too low, resulting in a significant increase in the viscosity of the emulsion.

[0058] The modifier exists in the form of a comonomer, which is characterized by having a low melt viscosity, which can significantly reduce the crystallinity and the viscosity at the melting point temperature. PTFE can still maintain extremely high viscosity at high temperatures (such as 380°C). Usually, the melt viscosity of PTFE is as high as 10GPa·s (1010Pa·s), which makes it unable to flow when melted. Some voids will remain in the products made of PTFE homopolymer, and these voids will affect the mechanical properties and creep properties of the final products. In order to achieve better mechanical properties and creep properties of PTFE products, these residual voids must be eliminated. To solve this problem, it is necessary to reduce the viscosity of PTFE and no longer have high crystallization. Therefore, the key solution is to add a small amount of comonomer modifier during PTFE polymerization to interfere with the crystal structure of PTFE and obtain a denser and better performance product. By controlling the time and amount of adding the modified monomer, core modification or shell modification can be achieved, improving the ease of resin processing and product quality. Modifiers can be hydrogen, methane, propane, carbon tetrachloride, such as perfluoromethyl vinyl ether (PMVE), perfluoroethyl vinyl ether (PEVE), perfluoropropyl vinyl ether (PPVE) and perfluorobutyl vinyl ether (PBVE, etc., which are mainly chain transfer agents that cannot be polymerized.

[0059] The perfluoro copolymer resin dispersion exists in the form of emulsion, with a mass content of 40% to 60%. One or both of fluorinated ethylene propylene copolymer (FEP) and tetrafluoroethylene-perfluoro copolymer (PFA) can be selected. Due to the fluorine-containing material component, this material can achieve good compatibility with PTFE membrane materials, and its surface has a certain degree of stickiness, which can be used as a transition material to achieve the adhesion between PTFE membrane materials and other materials.

[0060] Dispersants are non-ionic surfactants, such as Triton X-100 or Fluon GP1, which can be suspended in water and are negatively charged. They are used to improve the wettability of the resin and adjust the viscosity to achieve uniform distribution of the resin and other additives.

[0061] Defoaming agents are used to defoam water-based emulsions and reduce bubble defects in the final high-temperature products. Modified polysiloxane defoaming agents can be used as the main ones, such as BYK-024 or BYK-028.

[0062] The softener is a silicone resin with carbinol functional groups. An alcohol group is any group containing at least one hydroxyl group bonded to carbon, so an alcohol group may contain more than one COH group, and its general chemical formula is R-(CH3) x SiO y , R is a functional group with an alcoholic hydroxyl group. Specifically, the chemical formula of the silicone resin with a methanol functional group can be exemplified as (R 1 )(CH3)2SiO 0.5 ,R 1 =-(CH2)3OH, (R 2 )(CH3)SiO,R 2 =-(CH2)3C6H4OH. 1 and R 2 Among the alkyl groups there may be mentioned methyl, ethyl, propyl, butyl, pentyl, hexyl and octyl, wherein the alkyl group is typically methyl. 1 and R 2 Among the aromatic groups, phenyl, naphthyl, benzyl, tolyl, xylyl, biphenyl, methylphenyl, 2-phenylethyl, 2-phenyl-2-methylethyl, chlorophenyl, bromophenyl and fluorophenyl can be cited, among which the aromatic group is typically phenyl. Since the material contains alcohol functional groups and reactive components such as organosiloxane, it is compatible with both PTFE fluorine membrane materials and epoxy resin materials, and achieves strong interface bonding through hydrogen bonds and van der Waals forces. Therefore, the softener can not only improve the performance of PTFE membrane materials and make the membrane surface softer, but also improve the interface bonding strength between PTFE membrane materials and epoxy adhesives.

[0063] Embodiment 2:

[0064] This embodiment provides a method for preparing a modified PTFE fluorine membrane material, comprising the steps of:

[0065] S2-1, 10000 parts of TFE monomer, 5000 parts of deionized water, 2 parts of the first dispersant (ammonium perfluorooctanoate), 100 parts of the stabilizer (paraffin), and 0.1 parts of the initiator (ammonium persulfate) are put into a reactor for polymerization reaction;

[0066] The reaction temperature in the reactor was controlled to be 60°C, the pressure to be 3.5MPa, the stirring speed to be 100r / min, and the reaction time to be 10h;

[0067] When the polymerization reaction time reaches 70%, 1 part of a modifier (PMVE) is added into the reactor to prepare a PTFE emulsion with low viscosity.

[0068] S2-2, drying, baking and sintering the PTFE emulsion to obtain a PTFE membrane material; the specific steps are as follows:

[0069] S2-201. Fill the PTFE emulsion into each dipping tank of the first coating equipment, and allow the plain glass fiber cloth to flow from the initial position through each dipping tank through the winding and rolling action of the rollers of the first coating equipment, so that the surface of the plain glass fiber cloth is coated with the PTFE emulsion due to dipping, and then the PTFE emulsion is sintered and formed on the surface of the plain glass fiber cloth through the drying area, baking area, and sintering area of ​​the first coating equipment. After each time of emulsion dipping and high-temperature treatment, the PTFE coating can achieve a certain thickness increase.

[0070] S2-202, repeat the above steps for a preset number of times according to the thickness requirement of the PTFE membrane material to obtain the PTFE membrane material.

[0071] The temperature of the drying zone is 80°C, which is used to remove moisture from the emulsion coating; the temperature of the baking zone is 280°C, which is used to remove the coating surfactant; and the temperature of the sintering zone is 380°C, which is used for sintering and molding the PTFE coating. At the same time, the coating processing flow rate is set to 0.5 m / min. Too slow a speed will lead to a decrease in production efficiency and economic benefits, while too fast a speed may also cause the presence of coating blisters due to insufficient removal of moisture in the drying zone or insufficient removal of surfactants in the baking zone, which may increase the risk of fire in the sintering zone, as well as the risk of insufficient sintering and affecting product performance.

[0072] S2-3, 1 part of the second dispersant (Triton X-100) and 10 parts of deionized water were mixed and stirred at 70°C until the second dispersant was evenly dissolved and cooled to room temperature to form a mixed solution, and then 0.1 parts of a softener (organic silicone resin containing alcohol hydroxyl functional groups (CH2)3OH-(CH3)2SiO 0.5 ), 100 parts of a 40% by weight perfluoro copolymer resin dispersion (FEP emulsion) and 0.1 parts of a defoaming agent (BYK-024), stirred evenly, and filtered through a 200-mesh sieve to obtain a membrane surface treatment agent.

[0073] S2-4. Fill the membrane surface treatment agent into each dipping tank of the second coating equipment, and let the PTFE membrane flow from the initial position through each dipping tank through the winding and rolling action of the roller of the second coating equipment, so that the surface of the PTFE membrane is coated with the membrane surface treatment agent due to dipping, and then use a scraper to remove excess treatment agent. Then, after passing through the drying area, baking area, and sintering area of ​​the second coating equipment, the surface of the PTFE membrane is sintered into a thin surface treatment layer with a thickness of 10um, thereby finally obtaining a modified PTFE fluoromembrane material with good mechanical strength, creep performance and adhesion performance.

[0074] Embodiment 3:

[0075] This embodiment provides a method for preparing a modified PTFE fluorine membrane material, comprising the steps of:

[0076] S3-1, 10,000 parts of TFE monomer, 20,000 parts of deionized water, 20 parts of a first dispersant (ammonium perfluorooctanoate), 1,000 parts of a stabilizer (paraffin), and 1 part of an initiator (ammonium persulfate) are put into a reactor to carry out a polymerization reaction;

[0077] The reaction temperature in the reactor was controlled to be 60°C, the pressure to be 3.5MPa, the stirring speed to be 100r / min, and the reaction time to be 10h;

[0078] When the polymerization reaction time reached 70%, 10 parts of a modifier (PMVE) was added into the reactor to prepare a PTFE emulsion with low viscosity.

[0079] S3-2, drying, baking and sintering the PTFE emulsion to obtain a PTFE membrane material; the specific steps are as follows:

[0080] S3-201. Fill the PTFE emulsion into each dipping tank of the first coating equipment, and let the plain glass fiber cloth flow from the initial position through each dipping tank through the winding and rolling action of the roller of the first coating equipment, so that the surface of the plain glass fiber cloth is coated with PTFE emulsion due to dipping, and then the PTFE emulsion is sintered and formed on the surface of the plain glass fiber cloth through the treatment of the drying area, baking area and sintering area of ​​the first coating equipment. After each time of emulsion dipping and high-temperature treatment, the PTFE coating can achieve a certain thickness increase.

[0081] S3-202, repeat the above steps for a preset number of times according to the thickness requirement of the PTFE membrane material to obtain the PTFE membrane material.

[0082] The temperature of the drying zone is 80°C, which is used to remove moisture from the emulsion coating; the temperature of the baking zone is 280°C, which is used to remove the coating surfactant; and the temperature of the sintering zone is 380°C, which is used for sintering and molding the PTFE coating. At the same time, the coating processing flow rate is set to 0.5 m / min. Too slow a speed will lead to a decrease in production efficiency and economic benefits, while too fast a speed may also cause the presence of coating blisters due to insufficient removal of moisture in the drying zone or insufficient removal of surfactants in the baking zone, which may increase the risk of fire in the sintering zone, as well as the risk of insufficient sintering and affecting product performance.

[0083] S3-3, 5 parts of the second dispersant (Triton X-100) and 100 parts of deionized water were mixed and stirred at 70°C until the second dispersant was evenly dissolved and cooled to room temperature to form a mixed solution, and then 2 parts of a softener (organic silicone resin containing alcohol hydroxyl functional groups (CH2)3OH-(CH3)2SiO 0.5 ), 100 parts of a 60% by weight perfluoro copolymer resin dispersion (FEP emulsion) and 1 part of a defoamer (BYK-024), stir evenly, and filter using a 200-mesh sieve to obtain a membrane surface treatment agent.

[0084] S3-4. Fill the membrane surface treatment agent into each dipping tank of the second coating equipment, and let the PTFE membrane flow from the initial position through each dipping tank through the winding and rolling action of the roller of the second coating equipment, so that the surface of the PTFE membrane is coated with the membrane surface treatment agent due to dipping, and then use a scraper to remove excess treatment agent. Then, after passing through the drying area, baking area, and sintering area of ​​the second coating equipment, the surface of the PTFE membrane is sintered into a thin surface treatment layer with a thickness of 100um, thereby finally obtaining a modified PTFE fluoromembrane material with good mechanical strength, creep performance and adhesion performance.

[0085] Embodiment 4:

[0086] This embodiment provides a method for preparing a modified PTFE fluorine membrane material, comprising the steps of:

[0087] S4-1, 10000 parts of TFE monomer, 8000 parts of deionized water, 8 parts of the first dispersant (ammonium perfluorononanoate), 600 parts of the stabilizer (paraffin), and 0.8 parts of the initiator (potassium persulfate) are put into a reactor for polymerization reaction;

[0088] The reaction temperature in the reactor was controlled to be 50°C, the pressure to be 2MPa, the stirring speed to be 50r / min, and the reaction time to be 6h;

[0089] When the polymerization reaction time reached 80%, 6 parts of a modifier (PMVE) were added into the reactor to prepare a PTFE emulsion with low viscosity.

[0090] S4-2, drying, baking and sintering the PTFE emulsion to obtain a PTFE membrane material; the specific steps are as follows:

[0091] S4-201. Fill the PTFE emulsion into each dipping tank of the first coating equipment, and allow the plain glass fiber cloth to flow from the initial position through each dipping tank through the winding and rolling action of the rollers of the first coating equipment, so that the surface of the plain glass fiber cloth is coated with the PTFE emulsion due to dipping, and then the PTFE emulsion is sintered and formed on the surface of the plain glass fiber cloth through the drying area, baking area, and sintering area of ​​the first coating equipment. After each emulsion dipping and high-temperature treatment, the PTFE coating can achieve a certain thickness increase.

[0092] S4-202, repeat the above steps for a preset number of times according to the thickness requirement of the PTFE membrane material to obtain the PTFE membrane material.

[0093] The temperature of the drying zone is 80°C, which is used to remove moisture from the emulsion coating; the temperature of the baking zone is 280°C, which is used to remove the coating surfactant; and the temperature of the sintering zone is 380°C, which is used for sintering and molding the PTFE coating. At the same time, the coating processing flow rate is set to 1.0 m / min. Too slow a speed will lead to a decrease in production efficiency and economic benefits, while too fast a speed may also cause the presence of coating blisters due to insufficient removal of moisture in the drying zone or insufficient removal of surfactants in the baking zone, which may increase the risk of fire in the sintering zone, as well as the risk of insufficient sintering and affecting product performance.

[0094] S4-3. Mix 3 parts of the second dispersant (Fluon GP1) and 60 parts of deionized water at 50°C and stir until the second dispersant is evenly dissolved, and cool to room temperature to form a mixed solution. Then, slowly add 1.2 parts of a softener (organic silicone resin (CH2)3C6H4OH-(CH3)SiO containing alcohol hydroxyl functional groups), 100 parts of a perfluoro copolymer resin dispersion (PFA emulsion) with a mass content of 52%, and 0.7 parts of a defoaming agent (BYK-028) into the mixed solution in sequence according to a preset ratio, stir evenly, and filter using a 200-mesh sieve to obtain a membrane surface treatment agent.

[0095] S4-4. Fill the membrane surface treatment agent into each dipping tank of the second coating equipment, and let the PTFE membrane flow from the initial position through each dipping tank through the winding and rolling action of the roller of the second coating equipment, so that the surface of the PTFE membrane is coated with the membrane surface treatment agent due to dipping, and then use a scraper to remove excess treatment agent. Then, after passing through the drying area, baking area, and sintering area of ​​the second coating equipment, the surface of the PTFE membrane is sintered into a thin surface treatment layer with a thickness of 40um, thereby finally obtaining a modified PTFE fluoromembrane material with good mechanical strength, creep performance and adhesion performance.

[0096] Embodiment 5:

[0097] This embodiment provides a method for preparing a modified PTFE fluorine membrane material, comprising the steps of:

[0098] S5-1, 10,000 parts of TFE monomer, 15,000 parts of deionized water, 15 parts of a first dispersant (all-alkyl carboxylate), 800 parts of a stabilizer (paraffin), and 0.8 parts of an initiator (lithium persulfate) are put into a reactor to carry out a polymerization reaction;

[0099] The reaction temperature in the reactor was controlled to be 70°C, the pressure to be 4MPa, the stirring speed to be 120r / min, and the reaction time to be 16h;

[0100] When the polymerization reaction time reached 70%, 8 parts of a modifier (PMVE) were added into the reactor to prepare a PTFE emulsion with low viscosity.

[0101] S5-2, drying, baking and sintering the PTFE emulsion to obtain a PTFE membrane material; the specific steps are as follows:

[0102] S5-201. Fill the PTFE emulsion into each dipping tank of the first coating equipment, and allow the plain glass fiber cloth to flow from the initial position through each dipping tank through the winding and rolling action of the rollers of the first coating equipment, so that the surface of the plain glass fiber cloth is coated with the PTFE emulsion due to dipping, and then the PTFE emulsion is sintered and formed on the surface of the plain glass fiber cloth through the drying area, baking area, and sintering area of ​​the first coating equipment. After each emulsion dipping and high-temperature treatment, the PTFE coating can achieve a certain thickness increase.

[0103] S5-202. Repeat the above steps for a preset number of times according to the thickness requirement of the PTFE membrane material to obtain the PTFE membrane material.

[0104] The temperature of the drying zone is 80°C, which is used to remove moisture from the emulsion coating; the temperature of the baking zone is 280°C, which is used to remove the coating surfactant; and the temperature of the sintering zone is 380°C, which is used for sintering and molding the PTFE coating. At the same time, the coating processing flow rate is set to 3.0 m / min. Too slow a speed will lead to a decrease in production efficiency and economic benefits, while too fast a speed may also cause the presence of coating blisters due to insufficient removal of moisture in the drying zone or insufficient removal of surfactants in the baking zone, which may increase the risk of fire in the sintering zone, as well as the risk of insufficient sintering and affecting product performance.

[0105] S5-3. Mix 4 parts of the second dispersant (Triton X-100) and 80 parts of deionized water at 60°C and stir until the second dispersant is evenly dissolved, and cool to room temperature to form a mixed solution. Then, slowly add 1.4 parts of a softener (organic silicone resin C6H5CH2OH-(CH3)SiO containing alcohol hydroxyl functional groups), 100 parts of a perfluoro copolymer resin dispersion (PFA emulsion) with a mass content of 55%, and 0.6 parts of a defoaming agent (BYK-024) into the mixed solution in sequence according to a preset ratio, stir evenly, and filter using a 200-mesh sieve to obtain a membrane surface treatment agent.

[0106] S5-4. Fill the membrane surface treatment agent into each dipping tank of the second coating equipment, and let the PTFE membrane flow from the initial position through each dipping tank through the winding and rolling action of the roller of the second coating equipment, so that the surface of the PTFE membrane is coated with the membrane surface treatment agent due to dipping, and then use a scraper to remove excess treatment agent. Then, after passing through the drying area, baking area, and sintering area of ​​the second coating equipment, the surface of the PTFE membrane is sintered into a thin surface treatment layer with a thickness of 60um, thereby finally obtaining a modified PTFE fluoromembrane material with good mechanical strength, creep performance and adhesion performance.

[0107] Embodiment 6:

[0108] This embodiment provides a modified PTFE fluoromembrane material, which is prepared by the method of Embodiment 1, Embodiment 2, Embodiment 3, Embodiment 4 or Embodiment 5.

[0109] Embodiment 7:

[0110] like Figures 1 to 3 As shown, this embodiment provides a wind turbine blade, including the modified PTFE fluoromembrane material described in Example 6, the modified PTFE fluoromembrane material 1 is arranged in the trailing edge shell area of ​​the wind turbine blade by bonding, and is located between the main beam 2 and the trailing edge beam 3 of the wind turbine blade. The middle area of ​​the modified PTFE fluoromembrane material is supported by the transverse ribs 4 in the axial direction of the wind turbine blade, thereby reducing the weight and cost of the blade.

[0111] Comparative Example 1:

[0112] This embodiment provides a method for preparing a fluorine film material, wherein no modifier is used in the preparation process, and comprises the steps of:

[0113] D1-1, 10,000 parts of TFE monomer, 10,000 parts of deionized water, 5 parts of a first dispersant (ammonium perfluorooctanoate), 500 parts of a stabilizer (paraffin), and 0.5 parts of an initiator (ammonium persulfate) were put into a reactor for polymerization reaction;

[0114] The reaction temperature in the reactor was controlled to be 60° C., the pressure to be 3.5 MPa, the stirring speed to be 100 r / min, and the reaction time to be 10 h to obtain a PTFE emulsion with high viscosity.

[0115] D1-2. Fill the PTFE emulsion into each dipping tank of the coating equipment, and let the plain glass fiber cloth flow from the initial position through each dipping tank through the winding and rolling action of the roller of the coating equipment, so that the surface of the plain glass fiber cloth is coated with the PTFE emulsion due to dipping, and then the PTFE emulsion is sintered and formed on the surface of the plain glass fiber cloth through the treatment of the drying area, baking area and sintering area of ​​the coating equipment. After each time of emulsion dipping and high-temperature treatment, the PTFE coating can achieve a certain thickness increase. Repeat the above operation for a preset number of times according to the thickness requirement of the PTFE membrane material to obtain the PTFE membrane material.

[0116] Among them, the temperature of the drying zone is 80°C, the temperature of the baking zone is 280°C, the temperature of the sintering zone is 380°C, and the coating processing flow speed is set to 0.5 m / min.

[0117] D1-3, 3 parts of the second dispersant (Triton X-100) and 50 parts of deionized water were mixed and stirred at 70°C until the second dispersant was evenly dissolved and cooled to room temperature to form a mixed solution, and then 1 part of a softener (organic silicone resin containing alcohol hydroxyl functional groups (CH2)3OH-(CH3)2SiO 0.5 ), 100 parts of a perfluoro copolymer resin dispersion (FEP emulsion) with a mass content of 48% and 0.3 parts of a defoaming agent (BYK-024), stir evenly, and filter using a 200-mesh sieve to obtain a membrane surface treatment agent.

[0118] D1-4. Fill the membrane surface treatment agent into each dipping tank of the second coating equipment, and let the PTFE membrane flow from the initial position through each dipping tank through the winding and rolling action of the roller of the second coating equipment, so that the surface of the PTFE membrane is coated with the membrane surface treatment agent due to dipping, and then use a scraper to remove the excess treatment agent. Then, after passing through the drying area, baking area, and sintering area of ​​the second coating equipment, the surface of the PTFE membrane is sintered into a thin surface treatment layer with a thickness of 30um to obtain a fluorine membrane material.

[0119] Comparative Example 2:

[0120] This embodiment provides a method for preparing a fluorine film material, wherein no softener is used in the preparation process, comprising the steps of:

[0121] D2-1, 10,000 parts of TFE monomer, 10,000 parts of deionized water, 5 parts of the first dispersant (ammonium perfluorooctanoate), 500 parts of the stabilizer (paraffin), and 0.5 parts of the initiator (ammonium persulfate) were put into a reactor for polymerization reaction;

[0122] The reaction temperature in the reactor was controlled to be 60°C, the pressure to be 3.5MPa, the stirring speed to be 100r / min, and the reaction time to be 10h. When the polymerization reaction time reached 70%, the modifier PMVE was added into the reactor to obtain PTFE emulsion.

[0123] D2-2. Fill the PTFE emulsion into each dipping tank of the coating equipment, and let the plain glass fiber cloth flow from the initial position through each dipping tank through the winding and rolling action of the rollers of the coating equipment, so that the surface of the plain glass fiber cloth is coated with the PTFE emulsion due to dipping, and then the PTFE emulsion is sintered and formed on the surface of the plain glass fiber cloth through the treatment of the drying area, baking area and sintering area of ​​the coating equipment. After each time of emulsion dipping and high-temperature treatment, the PTFE coating can achieve a certain thickness increase. Repeat the above operation for a preset number of times according to the thickness requirement of the PTFE membrane material to obtain the PTFE membrane material.

[0124] Among them, the temperature of the drying zone is 80°C, the temperature of the baking zone is 280°C, the temperature of the sintering zone is 380°C, and the coating processing flow speed is set to 0.5 m / min.

[0125] D2-3. Mix 3 parts of the second dispersant (Triton X-100) and 50 parts of deionized water at 70°C and stir until the second dispersant is evenly dissolved, and cool to room temperature to form a mixed liquid. Then, slowly add 100 parts of a perfluoro copolymer resin dispersion (FEP emulsion) with a mass content of 48% and 0.3 parts of a defoaming agent (BYK-024) to the mixed liquid in sequence according to a preset ratio, stir evenly, and filter using a 200-mesh sieve to obtain a membrane surface treatment agent.

[0126] D2-4. Fill the membrane surface treatment agent into each dipping tank of the second coating equipment, and let the PTFE membrane flow from the initial position through each dipping tank through the winding and rolling action of the roller of the second coating equipment, so that the surface of the PTFE membrane is coated with the membrane surface treatment agent due to dipping, and then use a scraper to remove excess treatment agent, and then pass through the drying area, baking area, and sintering area of ​​the second coating equipment to sinter the surface of the PTFE membrane into a thin surface treatment layer. The thickness of the surface treatment layer is 30um, and the fluorine membrane material is obtained.

[0127] Comparative Example 3:

[0128] This embodiment provides a method for preparing a fluorine film material, wherein no perfluoro copolymer resin dispersion is used in the preparation process, and the method comprises the following steps:

[0129] D3-1, 10,000 parts of TFE monomer, 10,000 parts of deionized water, 5 parts of the first dispersant (ammonium perfluorooctanoate), 500 parts of the stabilizer (paraffin), and 0.5 parts of the initiator (ammonium persulfate) were put into a reactor for polymerization reaction;

[0130] The reaction temperature in the reactor was controlled to be 60°C, the pressure to be 3.5MPa, the stirring speed to be 100r / min, and the reaction time to be 10h. When the polymerization reaction time reached 70%, the modifier PMVE was added into the reactor to obtain PTFE emulsion.

[0131] D3-2. Fill the PTFE emulsion into each dipping tank of the coating equipment, and let the plain glass fiber cloth flow from the initial position through each dipping tank through the winding and rolling action of the rollers of the coating equipment, so that the surface of the plain glass fiber cloth is coated with the PTFE emulsion due to dipping, and then the PTFE emulsion is sintered and formed on the surface of the plain glass fiber cloth through the treatment of the drying area, baking area and sintering area of ​​the coating equipment. After each time of emulsion dipping and high-temperature treatment, the PTFE coating can achieve a certain thickness increase. Repeat the above operation for a preset number of times according to the thickness requirement of the PTFE membrane material to obtain the PTFE membrane material.

[0132] Among them, the temperature of the drying zone is 80°C, the temperature of the baking zone is 280°C, the temperature of the sintering zone is 380°C, and the coating processing flow speed is set to 0.5 m / min.

[0133] D3-3, 3 parts of the second dispersant (Triton X-100) and 50 parts of deionized water were mixed and stirred at 70°C until the second dispersant was evenly dissolved and cooled to room temperature to form a mixed solution, and then 1 part of the softener containing alcohol hydroxyl functional group silicone resin (CH2)3OH-(CH3)2SiO was slowly added to the mixed solution in accordance with the preset ratio. 0.5 and 0.3 parts of defoamer (BYK-024), stir evenly, and filter through a 200-mesh sieve to obtain a membrane surface treatment agent.

[0134] D3-4. Fill the membrane surface treatment agent into each dipping tank of the second coating equipment, and let the PTFE membrane flow from the initial position through each dipping tank through the winding and rolling action of the roller of the second coating equipment, so that the surface of the PTFE membrane is coated with the membrane surface treatment agent due to dipping, and then use a scraper to remove excess treatment agent, and then pass through the drying area, baking area, and sintering area of ​​the second coating equipment to sinter the surface of the PTFE membrane into a thin surface treatment layer. The thickness of the surface treatment layer is 30um, and the fluorine membrane material is obtained.

[0135] Comparative Example 4:

[0136] This embodiment provides a method for preparing a fluorine film material, wherein the film material surface is not treated during the preparation process, and comprises the following steps:

[0137] D4-1, 10,000 parts of TFE monomer, 10,000 parts of deionized water, 5 parts of the first dispersant (ammonium perfluorooctanoate), 500 parts of the stabilizer (paraffin), and 0.5 parts of the initiator (ammonium persulfate) were put into a reactor for polymerization reaction;

[0138] The reaction temperature in the reactor was controlled to be 60°C, the pressure to be 3.5MPa, the stirring speed to be 100r / min, and the reaction time to be 10h. When the polymerization reaction time reached 70%, the modifier PMVE was added into the reactor to obtain PTFE emulsion.

[0139] D4-2. Fill the PTFE emulsion into each dipping tank of the coating equipment, and let the plain glass fiber cloth flow from the initial position through each dipping tank through the winding and rolling action of the rollers of the coating equipment, so that the surface of the plain glass fiber cloth is coated with the PTFE emulsion due to dipping, and then the PTFE emulsion is sintered and formed on the surface of the plain glass fiber cloth through the treatment of the drying area, baking area and sintering area of ​​the coating equipment. After each time of emulsion dipping and high-temperature treatment, the PTFE coating can achieve a certain thickness increase. Repeat the above operation for a preset number of times according to the thickness requirement of the PTFE membrane material to obtain a fluorine membrane material.

[0140] Among them, the temperature of the drying zone is 80°C, the temperature of the baking zone is 280°C, the temperature of the sintering zone is 380°C, and the coating processing flow speed is set to 0.5 m / min.

[0141] The fluorofilm materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were tested for surface adhesion performance (T-peel strength - test standard ISO 11339; shear strength - test standard ISO 4587;), mechanical properties (bulk tensile strength - test standard GB / T 7689.5), creep performance test (bulk tensile creep - test method using 1 / 4 tensile strength to maintain load for 168h), wherein the adhesion performance specimens were tested after the film material was bonded to the glass fiber reinforced plastic by epoxy structural adhesive; the comparative analysis of the test results is shown in Table 1 below.

[0142]

[0143] Table 1 Comparison of film performance in the examples and comparative examples

[0144] Analyzing the above data, we can see that:

[0145] Comparing the embodiments with comparative example 1, since a modifier is used in the polymerization reaction of the modified PTFE fluoromembrane material, the bulk tensile strength and bulk creep performance of the membrane material are significantly improved, while in comparative example 1, no modifier is used, resulting in a decrease in the tensile strength of the membrane material of more than 40%, and an increase in the bulk tensile creep elongation of more than 5 times, resulting in a serious decline in performance.

[0146] Comparing the embodiments with Comparative Example 2, since no softener was used in the preparation process of the membrane surface treatment agent of Comparative Example 2, hydrogen bonds and van der Waals forces could not be established between the membrane and the epoxy structural adhesive, resulting in a decrease in T-peel strength of more than 30% and a decrease in shear strength of more than 50%.

[0147] Comparing the embodiments and comparative example 3, since the perfluoro copolymer resin dispersion is not used in the preparation process of the membrane surface treatment agent of comparative example 3, the membrane and the epoxy structural adhesive cannot form good compatibility and adhesion through the fluorine-based transition material, resulting in a decrease in T-peel strength of more than 40%; and a decrease in shear strength of more than 60%.

[0148] Comparing the embodiments with comparative example 4, since comparative example 4 does not perform surface treatment on the membrane material, no effective bonding interface can be established between the membrane material and the epoxy structural adhesive, resulting in a decrease in T-peel strength of more than 80% and a decrease in shear strength of more than 85%.

[0149] In summary, the present invention obtains a modified PTFE fluoromembrane material with high surface adhesion performance, improved material strength and enhanced creep performance through the application and process treatment of different materials in different processes. The modified PTFE fluoromembrane material is suitable for wind turbine blades and can achieve weight reduction and cost reduction of blades and wind turbines.

[0150] The above is only a preferred embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and invention concept of the present invention within the scope disclosed by the present invention, which shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a modified PTFE fluorine membrane material, characterized in that: Including steps, Putting TFE monomer, deionized water, a first dispersant, a stabilizer and an initiator into a reactor according to a preset ratio to carry out a polymerization reaction, and adding a modifier into the reactor when the polymerization reaction reaches a preset time to prepare a PTFE emulsion with low viscosity; Drying, baking and sintering the PTFE emulsion to obtain a PTFE membrane material; The second dispersant and deionized water are mixed and stirred at a preset temperature according to a preset ratio, and then cooled to room temperature to prepare a mixed liquid, and a softener, a perfluoro copolymer resin dispersion and a defoamer in a preset ratio are sequentially added to the mixed liquid and stirred evenly to obtain a membrane surface treatment agent; The membrane surface treatment agent is coated on the PTFE membrane material, and the PTFE membrane material is dried, baked and sintered to obtain a modified PTFE fluorine membrane material.

2. The method for preparing the modified PTFE fluorine membrane material according to claim 1, characterized in that: The specific steps of adding TFE monomer, deionized water, a first dispersant, a stabilizer and an initiator into a reactor according to a preset ratio to carry out a polymerization reaction, and adding a modifier into the reactor when the polymerization reaction reaches a preset time to prepare a PTFE emulsion with a low viscosity are as follows: Put TFE monomer, deionized water, a first dispersant, a stabilizer and an initiator into a reaction kettle according to the ratio of 10,000 parts of TFE monomer, 5,000 to 20,000 parts of deionized water, 2 to 20 parts of the first dispersant, 100 to 1,000 parts of the stabilizer and 0.1 to 1 part of the initiator to carry out a polymerization reaction; Control the reaction temperature in the reactor to be 40°C to 90°C, the pressure to be 2 to 5MPa, the stirring speed to be 50 to 200r / min, and the reaction time to be 6 to 24h; When the polymerization reaction time reaches 50% to 80%, 1 to 10 parts of a modifier are added into the reactor to prepare a PTFE emulsion with low viscosity.

3. The method for preparing the modified PTFE fluorine membrane material according to claim 2, characterized in that: The first dispersant is one of peralkyl carboxylates, fluoroalkyl carboxylates, and perfluorooctane sulfonates; the stabilizer is a water-insoluble saturated hydrocarbon with more than 12 carbon atoms; the initiator is an ionic inorganic initiator; and the modifier is perfluoromethyl vinyl ether, perfluoroethyl vinyl ether, perfluoropropyl vinyl ether, or perfluorobutyl vinyl ether.

4. The method for preparing the modified PTFE fluorine membrane material according to claim 1, characterized in that: The specific steps of drying, baking and sintering the PTFE emulsion to obtain the PTFE membrane material are as follows: S201, filling PTFE emulsion into each dipping tank of the first coating equipment, allowing the plain glass fiber cloth to flow from the initial position through each dipping tank through the winding and rolling action of the roller of the first coating equipment, so that the surface of the plain glass fiber cloth is coated with PTFE emulsion due to dipping, and then sintering the PTFE emulsion on the surface of the plain glass fiber cloth through the treatment of the drying area, baking area, and sintering area of ​​the first coating equipment; S202, repeating step S201 for a preset number of times according to the thickness requirement of the PTFE membrane material to obtain the PTFE membrane material.

5. The method for preparing the modified PTFE fluorine membrane material according to claim 4, characterized in that: The temperature of the drying zone is 80°C to 95°C, the temperature of the baking zone is 250°C to 315°C, and the temperature of the sintering zone is 360°C to 400°C.

6. The method for preparing the modified PTFE fluorine membrane material according to claim 1, characterized in that: The specific steps of mixing the second dispersant and deionized water according to a preset ratio at a preset temperature and stirring, cooling to room temperature, and preparing a mixed liquid, and sequentially adding a softener, a perfluoro copolymer resin dispersion, and a defoamer in preset ratios to the mixed liquid and stirring evenly to obtain the membrane surface treatment agent are as follows: The second dispersant and deionized water are mixed and stirred at 50°C to 80°C according to a preset ratio until the second dispersant is evenly dissolved, and the mixture is cooled to room temperature to form a mixed liquid, and then a softener, a perfluoro copolymer resin dispersion and a defoamer are sequentially added to the mixed liquid according to a preset ratio, stirred evenly, and filtered using a mesh screen to obtain a membrane surface treatment agent; The preset ratio is: 100 parts of perfluoro copolymer resin dispersion, 1 to 5 parts of second dispersant, 0.1 to 1 part of defoaming agent, 0.1 to 2 parts of softener, and 10 to 100 parts of deionized water.

7. The method for preparing the modified PTFE fluorine membrane material according to claim 6, characterized in that: The perfluoro copolymer resin dispersion is one or two of a fluorinated ethylene propylene copolymer and a tetrafluoroethylene-perfluoro copolymer with a mass content of 40% to 60%; the second dispersant is a nonionic surfactant; the defoamer is a modified polysiloxane defoamer; and the softener is a silicone resin with a methanol functional group.

8. The method for preparing the modified PTFE fluorine membrane material according to claim 1, characterized in that: The specific steps of coating the membrane surface treatment agent onto the PTFE membrane material, and drying, baking and sintering the PTFE membrane material to obtain the modified PTFE fluorine membrane material are as follows: The membrane surface treatment agent is filled into each dipping tank of the second coating equipment, and the PTFE membrane is passed through each dipping tank from the initial position through the winding and rolling action of the roller of the second coating equipment, so that the surface of the PTFE membrane is coated with the membrane surface treatment agent due to dipping, and then the surface of the PTFE membrane is sintered into a surface treatment layer of a preset thickness after being treated in the drying area, baking area and sintering area of ​​the second coating equipment, thereby finally obtaining a modified PTFE fluoromembrane material.

9. A modified PTFE fluorine membrane material, characterized in that: The method is used to prepare the product according to any one of claims 1 to 8.

10. A wind turbine blade, characterized in that: It includes the modified PTFE fluoromembrane material as described in claim 9, which is arranged in the trailing edge shell area of ​​the wind turbine blade by bonding, and is located between the main beam and the trailing edge beam of the wind turbine blade, and the middle area of ​​the modified PTFE fluoromembrane material is supported by transverse ribs in the axial direction of the wind turbine blade.